Radiotherapy isocenters verified by matching to bony landmarks of the canine and feline head differ when localized using volumetric versus planar imaging. (13th August 2019) - Magestro, Leanne M.; Cahoon, Joyce Y.; Gieger, Tracy L.; Nolan, Michael W.
Abstract: The "gold standard" for verification of patient positioning before linear accelerator‐based stereotactic radiation therapy is kilovoltage cone‐beam computed tomography (kV‐CBCT), which is not uniformly available or utilized; planar imaging is sometimes used instead. The primary aim of this study was to determine if the position of the bony skull, when used as a surrogate for isocenter verification, is different when orthogonal megavoltage (MV) portal or kilovoltage (kV/kV) radiographs are used for image guidance, rather than kV‐CBCT. A secondary aim was to determine the influence of intra‐observer variability, body size and skull conformation on positioning, as determined using these three imaging modalities. Dogs and cats receiving radiotherapy of the head were recruited for this prospective analytical study. Planar (MV portal and kV/kV images) and volumetric (kV‐CBCT) images were acquired before treatment, and manually coregistered with reference images. Differences in skull position when matched based on MV portal, kV/kV images and kV‐CBCT were compared. A total of 65 subjects and 148 unique datasets were evaluated. The Wilcoxon rank‐sum test was used to evaluate effects of transitioning between imaging modalities. When comparing magnitude of shifts in MV to kV‐CBCT, MV to kV/kV and kV/kV to kV‐CBCT, there were statistically significant differences. Results were not measurably impacted by body size, skull conformation or interobserver differences. Based on shift magnitude and direction, an isotropic setup margin of at least 1 mm should be incorporated within the planning target volume when MV or kV planar imaging is used for position verification.